2009
DOI: 10.1039/b906058h
|View full text |Cite
|
Sign up to set email alerts
|

The Baeyer–Villiger reaction: solvent effects on reaction mechanisms

Abstract: This study focuses on the Baeyer-Villiger reaction of propanone and performic acid, with formic acid as catalyst. Continuum solvation methods (EIF-PCM and CPCM) and two density functionals (B3LYP and MPWB1K) are used to study solvent effects on two types of reaction mechanisms: concerted non-ionic and stepwise ionic. The ionic mechanism is the one found in most organic chemistry textbooks; it begins with the protonation of the ketone by the acid catalyst, even though this reaction normally takes place in non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 46 publications
15
41
0
Order By: Relevance
“…These corrections are in good agreement with those independently obtained by Ardura et al [88] and have been successfully used by other authors [89][90][91].…”
Section: Computational Detailssupporting
confidence: 88%
“…These corrections are in good agreement with those independently obtained by Ardura et al [88] and have been successfully used by other authors [89][90][91].…”
Section: Computational Detailssupporting
confidence: 88%
“…Therefore, among a variety of examined solvents, based on the results of Table 2, chloroform was selected as the ideal solvent in these series because the B-V oxidation of ketones proceeded more smoothly. Consequently, these findings are in good agreement with the well-known B-V oxidation mechanism, which involves two steps; the addition step seems to be ionic and the migration step, which is rate-determining, uncatalyzed, non-ionic and fully concerted [27]. It should be also mentioned that, stirring and heating the reaction mixture for 9 h at 80°C under solvent free conditions, was not complete at all (Entry 10).…”
Section: Effect Of Solventsupporting
confidence: 87%
“…Recently, both theoretical and experimental investigations proved that BV oxidation reactions could be accelerated in the presence of acids. The acid molecule was assumed to act as both proton donor and acceptor, decreasing the activation barrier of the addition step 13a,e,f,i,j. Meanwhile, our experiments also indicated that the BV oxidation reaction between 1 a and m ‐CPBA could occur even without the Sc III – N , N ′‐dioxide complex, affording racemic products in a yield of 19 % 19.…”
Section: Resultsmentioning
confidence: 65%